2021
DOI: 10.3389/pore.2021.584710
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Comparison of Anti-Tumoral Potential of Wharton’s Jelly and Bone Marrow Mesenchymal Stem Cells Exhibited by Cell Cycle Arrest in Glioma Cells (U87MG)

Abstract: The therapeutic potential of mesenchymal stem cells (MSCs) for various malignancies is currently under investigation due to their unique properties. However, many discrepancies regarding their anti-tumoral or pro-tumoral properties have raised uncertainty about their application for anti-cancer therapies. To investigate, if the anti-tumoral or pro-tumoral properties are subjective to the type of MSCs under different experimental conditions we set out these experiments. Three treatments namely cell lysates (CL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 73 publications
0
6
1
Order By: Relevance
“…In addition, MSCs integrated with tumor cells and had a significant inhibitory effect on the proliferation of malignant pleural mesothelioma cells [ 67 ]. Aslam et al showed that MSC lysates (Wharton’s Jelly and bone marrow) induced a general inhibitory effect on the proliferation of glioma cells and fibroblasts [ 68 ].…”
Section: Antitumor Properties Of Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…In addition, MSCs integrated with tumor cells and had a significant inhibitory effect on the proliferation of malignant pleural mesothelioma cells [ 67 ]. Aslam et al showed that MSC lysates (Wharton’s Jelly and bone marrow) induced a general inhibitory effect on the proliferation of glioma cells and fibroblasts [ 68 ].…”
Section: Antitumor Properties Of Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…The MSC-derived secretome can also exhibit cell cycle arrest in GB cells [ 95 ]. Moreover, cytotoxic cell death can be achieved by MSCs with expressed tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL).…”
Section: Cell Therapy For Glioblastomamentioning
confidence: 99%
“…Earlier findings about anti-tumor properties of MSC secretomes were done using conditioned medium (CM) of MSC cultures to treat cancer cells. There are reports on the inhibitory effects of UC-MSC CM on C6 glioma cell growth [ 154 ], inhibitory effects of AT-MSC and UC-MSC CM on U251 glioma cell proliferation, migration, and invasion [ 155 ], stimulatory effects of BM-MSC and UC-MSC CM on GBM stem-like cells’ response to temozolomide (TMZ) and cell-cycle arrest [ 156 ], and stimulatory effects of BM-MSC and WJ-MSC CM on U87 cell cell-cycle arrest [ 157 ]. A more recent study specifically used the exosomes isolated from CM of UC-MSCs, which expressed an inhibitory effect on U87 cell growth [ 158 ].…”
Section: Current Status Of Msc-ev Therapeutic Applications In the Brainmentioning
confidence: 99%